2020
DOI: 10.1007/s00261-020-02648-7
|View full text |Cite
|
Sign up to set email alerts
|

Higher frequency of hepatic steatosis at CT among COVID-19-positive patients

Abstract: Purpose Recent studies have demonstrated that obesity is significantly associated with increased disease severity, hospitalizations and mortality in COVID-19, with a potential role in the pathogenesis and prevalence in the new pandemic. The association with hepatic steatosis, however, a condition closely related to obesity within the spectrum of systemic metabolic dysfunctions, remains to be elucidated. We aimed to evaluate the frequency of hepatic steatosis as incidentally detected in chest CT examinations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 36 publications
1
50
2
3
Order By: Relevance
“…The proportion of liver injury was also higher in patients with severe COVID-19 (63). Periportal necrosis, lymphocytic infiltration of the sinusoids, dense portal infiltration by abnormally small lymphocytes, central vein thrombosis, and cirrhotic changes with thick fibrosis were all findings at liver autopsy (64,65).…”
Section: Abdominal Solid Organ Manifestations Liver and Biliary Manifmentioning
confidence: 92%
See 1 more Smart Citation
“…The proportion of liver injury was also higher in patients with severe COVID-19 (63). Periportal necrosis, lymphocytic infiltration of the sinusoids, dense portal infiltration by abnormally small lymphocytes, central vein thrombosis, and cirrhotic changes with thick fibrosis were all findings at liver autopsy (64,65).…”
Section: Abdominal Solid Organ Manifestations Liver and Biliary Manifmentioning
confidence: 92%
“…Periportal edema may be more apparent at both CT and MRI (Fig 16). There has also been increased prevalence of hepatic steatosis in patients with COVID-19 that is likely attributable to the known association between infection and obesity (64). In fact, it has been reported that hepatic steatosis is an independent risk factor of severe disease (67).…”
Section: Abdominal Solid Organ Manifestations Liver and Biliary Manifmentioning
confidence: 99%
“…Other authors have proposed that the increased levels of inflammatory mediators, such as IL-1, IL-6, and IL-10 levels, may further contribute to damaging hepatocytes in COVID-19 patients [1]. Hepatic steatosis is a commonly observed finding in patients testing positive for SARS-CoV-2 [2]. The effect of fatty liver on the severity of COVID-19 illness has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that MAFLD patients often suffer from hypertension, insulin resistance and type 2 diabetes, their specific position during the SARS epidemics was and is largely unknown. Furthermore, COVID-19 patients show a higher occurrence of hepatic steatosis measured by thorax CT (Kreling et al 2020) and SARS-CoV and SARS-CoV-2 infections are often accompanied by abnormal levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) serum levels which suggest liver damage (Zhang et al 2020;Cui et al 2004). In addition, suffering from MAFLD increases the risk for developing severe COVID-19 in both diabetic and non-diabetic patients (Gao et al 2020;Dongiovanni et al 2020;Pan et al 2020).…”
Section: Mafld and Covid-19 Are Interrelatedmentioning
confidence: 99%